The quasi-moderating role of organizational culture in the relationship between rewards and knowledge shared and gained - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2014)
Purpose - The purpose of this paper is to clarify the role of organizational culture and rewards in stimulating the sharing and gaining of knowledge. Design/methodology/approach - Hierarchical regression using survey data. Findings - The analyses show that rewards and organizational culture of knowledge transfer influence the knowledge shared and knowledge gained. Moreover, culture and rewards interact to influence knowledge gained, but not knowledge shared which leads to the conclusion knowledge gaining can be induced by rewards, even in the absence of a supportive culture. Research limitations/implications - The findings are consistent with socio-technical theory (STT) and the discussion positions this perspective as useful for future knowledge management studies. This research confirms that knowledge sharing and gaining are uniquely different activities that respond differently to culture and rewards. Originality/value - This study combines the work of different fields by focusing on knowledge sharing and gaining in a single study Through this process, a bridge between organizational learning theory and STT is revealed.
Keywords: Knowledge sharing; Innovation; Organizational culture; Knowledge creation; Knowledge transfer; Rewards; Knowledge gained; COMPETITIVE ADVANTAGE; MANAGEMENT-PRACTICES; WEAK TIES; INNOVATION; IDENTIFICATION; DETERMINANTS; PERFORMANCE; COMPLEXITY; PRINCIPLES; NETWORKS